INTERRELATION OF ENDOTHELIAL DYSFUNCTION GENE POLYMORPHISM WITH THE RISK OF DEVELOPING CHRONIC VENOUS INSUFFICIENCY OF THE VEINS OF THE LOWER EXTREMITIES - Vasilevsky E. A.; Aleinik V. A.; Musashaikhov Kh.T.; Dadabaev O. T . (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
Chronic venous insufficiency (CVI) is an important medical problem in developed countries. It was important to determine one of the leading roles in the pathogenesis of CVI, the interaction of matrix metalloproteinases (MMPs) as important mediators of the degenerative process and vascular endothelial growth factor (VEGFA). The study included 98 patients aged 20 to 78 years with chronic venous insufficiency, including, in accordance with the CEAP (Clinical-Etiological-Anatomical-Pathophysiological) classification, 45 patients with moderate CVI (class C3-C4) and 53 patients with severe CVI (class C5-C6). The results obtained in the course of the study reliably indicate the presence of an association between the carriage of the Arg allele and the Gln/Arg and Arg/Arg genotypes of the Gln279Arg polymorphism in the MMP9 gene, as well as the carriage of the T allele and the C/T and T/T genotypes of the C936T polymorphism in the VEGFA gene with the risk of developing complicated forms of CVI.